TECHNOLOGY AND ITS ROLE IN INNOVATIVE DEVELOPMENT OF SOCIETY - Mikhail E. Popov (Advanced Engineering Research, 2011)
The basic concepts of technology, its classification, and its role in the world economy globalization are considered. The conception of technological modes, where the role of the innovations in the technological mode change is specified, is disclosed. The correlation of the technological and economic development of the society is shown. The concept content of technological limit and technology gap is stated.